أثر الاعتدال في دالة الاستهلاك إسلاميا في جانب الاستثمار والإنتاج والتنمية المجتمعية = Being moderate in consumption and its effect on investment, production and societal development, in the context of Islam - Al-Jahdami, Ali bin Sulayman bin Muhammad; Amanullah, Muhammad (IIUM Press, 2022)
The research seeks to clarify the effect of moderation in consumer behaviour, and the extent to which moderation affects other economic activities. The economic activities are linked to each other, and this link can be seen in the effect of moderate consumption in them. This research aims to explain consumption from an Islamic perspective, and its difference from the conventional perspective, and to show the economic effects of moderation in consumption from an Islamic perspective. The researchers relied on the descriptive approach for explaining consumer behaviour from an Islamic perspective and its difference from the conventional perspective, then they analysed and studied this behaviour so that the effect of moderation in other economic activities becomes clear. The researchers concluded that consumption from an Islamic perspective, which is regulated by Islamic rulings, shows positive impact on the economy, with the increase in the aggregate demand for consumption and the higher marginal tendency to consume more than the conventional man-made perspective. This leads to increase the investment in the market as a result of transferring part of the income of the rich to the poor with various expenses, including zakāh, whose amount increases due to moderation. This results in raising the level of sufficiency in society, allocating resources, increasing employment and job opportunities, and protecting the economy from business cycles. It encourages thoughtful and bold investment and motivates the rich to choose the best alternative investment opportunity. The effect of moderation in consumption also appears in the development of consumption control in a way that it creates surpluses that increase investment, leads to improving the production in quantity and quality, and directs it towards considering the order of priorities.